Religion in a globalized world (Eurasian Journal of Religious Studies, 2017)
In this work the religion problem in the globalized world is described, the main problems of modern religion from the point of view of a ratio of political sphere of life, society and religion, relationship between various religions and improvement of relationship between people of all world community.In modern world, humanity has reached the enormous scientific and technological progress, which is not compatible with the moral understanding of many people, and the consequences of human actions. When humanity faces the threat of self-destruction, a science without religion does not solve today's problems that ultimately leads to the new way of development of the various religious communities. The phenomenon of religion and belief does not run its course and could not go out of the relevance and importance in the future, while humanity has not yet come to a consensus on peace and harmony.